The Effect of Time Pressure and Workload on Auditor Performance with Professional Ethics as a Moderating Variable at the West Kalimantan Audit Board - Tegar Laksono; Elok Heniwati; Haryono Haryono; Rusliyawati Rusliyawati; Juanda Astarani (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to analyze the influence of time pressure and workload on auditor performance as well as the role of professional ethics as a moderating variable in these relationships. Data were collected through questionnaires distributed to auditors at the Financial Supervisory Agency (BPK) of West Kalimantan Province. The analysis method used is Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS4 software to examine the relationships among variables. The results indicate that time pressure and workload have a significant negative effect on auditor performance. Furthermore, professional ethics was found to moderate the relationship between time pressure and workload with auditor performance, where auditors with a high level of professional ethics are able to maintain performance quality despite facing high pressure and workload. These findings emphasize the importance of strengthening professional ethics values as a protective factor to enhance auditors’ resilience against work-related stress. The practical implications of this study include the need for effective workload management and realistic scheduling, as well as the continuous development of professional ethics training to maintain audit quality and auditor well-being.